Особливості портретописання і характеротворення у повісті «Краса і сила» Володимира Винниченка - Золотюк, Л. (Літературознавчі обрії. Праці молодих учених, 2010)
The article examines the portraits of the characters of the story «The Beauty and the Strength» in the context of mutual relations between characters, connections between the portrait and the landscape, between symbols in the context of nonverbal communication. This article also points out the artistic means of portrait writing and draws the parallel «the portrait – the character».